Evaluation of Educational Situation of Rehabilitation Branches in Welfare and Rehabilitation University from the Student\'s Viewpoint in Educational Year 2003-2004 - Kianoush A'bdi; Sadat Seyyed Bagher Maddah; Mehdi Rahgozar; Asghar Dalvandi (University of Social Welfare and Rehabilitation Sciences, 2007)
Objective: This Study was aimed to determine the educational situation of rehabilitation branches in welfare and Rehabilitation University. Materials & Methods: This descriptive evaluation was performed using the viewpoints of undergraduate students studying in 3rd and 4th year together with the postgraduates in their 2 nd year that practiced the census of 160 students. The data was gathered using the questionnaire with the collaboration of studernts' representatives and analysed utilizing the likurt Index through the correlation coefficient. Results: Final findings of this research showed that the situation of evaluation for each educational heading is as follows: The situation of location for theoretical classess " rather desirable" and for practical classes "rather desirable". The Situation of practical classes "undesirable" , The status of classes affairs office "rather desirable" the status of educational experts "rather desirable" , the situation of lessons planning "undesirable" , the situation of presenting the theoretical lessons "rather desirable " the situation of education in clinical centers " undesirable" and the situation of clinical centers "undesirable". Conclusion: From all the student's viewpoints it concludes that situation of classes location, status of classes affairs office and, quality of theoretical classes are rather desirable but situation of practical classes and quality of clinical education are undesirable. Among educational groups speechtherapy department had better than others.